2019
DOI: 10.1371/journal.pone.0218852
|View full text |Cite
|
Sign up to set email alerts
|

Zinc deficiency and advanced liver fibrosis among HIV and hepatitis C co-infected anti-retroviral naïve persons with alcohol use in Russia

Abstract: Background and aims Liver disease in people living with HIV co-infected with hepatitis C virus is a source of morbidity and mortality in Russia. HIV accelerates liver fibrosis in the setting of HCV co-infection and alcohol use. Zinc deficiency is common among people living with HIV and may be a factor that facilitates the underlying mechanisms of liver fibrosis. We investigated the association between zinc deficiency and advanced liver fibrosis in a cohort of HIV/HCV co-infected persons reporting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 35 publications
0
21
0
Order By: Relevance
“…The antiviral property of zinc has been studied extensively in various viral infections, including coronavirus, hepatitis C virus, and HIV (Barocas et al, 2019). However, the exact role of zinc in SARS-CoV-2 is not well studied.…”
Section: Introductionmentioning
confidence: 99%
“…The antiviral property of zinc has been studied extensively in various viral infections, including coronavirus, hepatitis C virus, and HIV (Barocas et al, 2019). However, the exact role of zinc in SARS-CoV-2 is not well studied.…”
Section: Introductionmentioning
confidence: 99%
“…This limits the external validity of their findings and the generalizability of their results. Two of the articles engaged further analysis: exploratory [ 31 ] and sensitivity [ 32 ].…”
Section: Resultsmentioning
confidence: 99%
“…Zinc (Zn): Two of the studies [ 29 , 31 ] investigated the relationship between Zn and the development of condyloma acuminata and advanced liver cirrhosis in HIV-positive patients, respectively, while Li et al [ 33 ] assessed the association between semen quality of HIV-positive men and the concentration of seminal Zn. One of the studies [ 29 ] revealed that the mean plasma Zn levels were significantly lower in condyloma acuminata patients with HIV infection than those without HIV infection, with the difference in mean plasma Zn levels of 7.31 μg/dL (95% CI 2.25–12.37, p < 0.05).…”
Section: Resultsmentioning
confidence: 99%
“…The world is now facing a serious pandemic, caused by the Severe Acute Respiratory Syndrome Coronavirus-2 (SARS-CoV-2), also known as the novel Coronavirus Disease 2019 (COVID- 19). There is an urgent need for pharmacological, traditional, and complementary medicine approaches and nutritional intervention to aid in prevention, treatment, and recovery from the infection.…”
Section: Zinc In Respiratory Health: Sars-cov-2 Infectionmentioning
confidence: 99%
“…Zinc is essential for the development and activation of T-lymphocytes, which are the leading cells for defense against viral infections [18]. The antiviral property of zinc has been studied extensively in hepatitis C virus, coronavirus, human immunodeficiency virus and others [19].…”
Section: Zinc In Respiratory Health: Sars-cov-2 Infectionmentioning
confidence: 99%